"Omics" technologies for the certification of organic vegetables: Consumers' orientation in Italy and the main determinants of their acceptance. (November 2022) - Castellini, Greta; Sesini, Giulia; Iannello, Paola; Lombi, Linda; Lozza, Edoardo; Lucini, Luigi; Graffigna, Guendalina
Abstract: Traceability of food is considered as an important tool for ensuring food quality and safety, in turn increasing consumers' trust. Verification of food authenticity is currently carried out by officials and producers, typically through the use of paper documents that may not ensure a proper level of integrity. Therefore, independent analytical methods and forgery-proof labels are required by the agri-food sector, driving the development of "omics" traceability technologies for the authentication of foods. Despite the growing interest in these technologies from a technical-scientific point of view, no research has been carried out on consumers' perceptions. Given these premises, this study aimed at understanding consumers' orientations towards "omics" technologies applied to organic vegetables and unravelling the main psychological and socio-demographic variables that influence their adoption. Data were collected with a self-report questionnaire filled out by a sample of 807 Italians, representative of the population. We used descriptive statistics and multiple linear regression to analyze data. Results show that, despite the lack of subjective knowledge of "omics" technologies, Italians have positive attitudes and are interested in using and buying organic vegetables certified by this approach, even paying more. Furthermore, young people with positive attitudes and higher environmental concerns have a more positive attitude towards "omics" technologies. This research points out the need to educate consumers about what the "omics" technology is, enhancing consumers' attitudes and underlining its environmental contribution. This will increase consumers' acceptance and support the implementation of the technology. Highlights: Italians have positive attitudes towards "omics" technologies. Italians are prone to use and buy organic vegetables certified by this approach. Italians are willing to pay more for organic vegetables certified by this approach. Environmental concern impacts on the use of these technologies. The need to educate consumers about what the "omics" technologies are.